Delivering climate services for farmers and pastoralists through interactive radio - Hampson, Karen J.; Chapota, Rex; Emmanuel, Japhet; Tall, Arame; Huggins-Rao, Sheila; Leclair, Mark; Perkins, Kevin; Kaur, Harneet; Hansen, James (2015)
A scoping study to assess demand, opportunities and potential for the use of interactive radio to deliver climate services at scale for farmers and pastoralists was conducted by CCAFS in partnership with Farm Radio International in Tanzania, and Farm Radio Trust in Malawi in late 2014. Over 1280 individuals were interviewed in an audience research activity, while a desk survey, key informant interviews and knowledge partner engagement activities were undertaken to validate audience research and assess the wider context. The study reveals that for both Malawi and Tanzania, there is clear demand for climate information services via radio and mobile phone. Both radio and mobile phones are in common use, and are rated by farmers and pastoralists to have great potential as effective and trusted channels where they can access various climate information services. Surveyed farmers and pastoralists noted that radio programs, backed up by ICT services, would serve them best. Rainfall patterns, temperature data and forecasting services – both weekly and daily – were mentioned as particular needs. In general, farmers would trust climate information received via their preferred radio stations, and would use it in decision-making on their farms. Women and men differed in time spent listening to radio, in mobile phone airtime purchased, and in Malawi, phone ownership; but larger location differences masked any gender differences in preferences about information content, delivery channels, or expectations about user and benefit. As a response to farmer articulated demand, Farm Radio International and Farm Radio Trust propose working with key institutions and radio station partners to develop interactive programming for rural climate services as part of their implementation of the GFCS Adaptation Programme in Africa. Interactive climate services radio programming would respond to farmers’ ongoing climate information needs, and will engage them in program design, broadcast, monitoring and evaluation – together with partner radio stations. Interactive climate services radio programming will consist of short weekly radio programs, with the option of daily forecasts or interpretations, and will be complemented with ICT services via mobile phone. Programs will be continuously monitored and assessed by audiences and project staff to ensure relevance, usefulness, level of use and accuracy.